CRISPR-Cas13: A new technology for the rapid detection of pathogenic microorganisms - Huang, Zhanchao; Fang, Jianhua; Zhou, Min; Gong, Zhenghua; Xiang, Tianxin (Frontiers in Microbiology, 2022)
Abstract: Pathogenic microorganisms have a critical impact on human lives. Rapid and sensitive diagnostic tools are urgently needed to facilitate the early treatment of microbial infections and effective control of microbial transmission. CRISPR-Cas13 of programmable RNA occurs with stronger sensitivity, great specificity, and high base resolution and thus provides a novel tool to rapid microorganisms detection. The review aims to summarize the characteristics of effectors of the CRISPR-Cas13 system and to illustrate the latest research into its application in the rapid detection of pathogenic microorganisms in combination with nucleic acid extraction, isothermal amplification and products detection, hoping to provide insights to spur further development.